Formulation and quality control of semi-solid containing harmless bacteria by-products: chronic wounds pro-healing activity - Sesto Cabral, María Eugenia (2015)
Chronic wounds are those that remain in a chronic inflammatory state and fail to follow normal healing process. Infection is one of the most important causes of chronicity. A frequent pathogen isolated from chronic infections is Pseudomonas aeruginosa; refractory to therapy and host immune attack in its biofilm phenotype. Lactobacillus plantarum cultures supernatants (LAPS) interfere with its pathogenic capacity. In addition, LAPS showed bacteriostatic and bactericide properties and is neither cytotoxic nor an inductor of necrosis-apoptosis. LAPSs chemical composition was determined; allowing us to propose a correlation between its constituents and their biological activity. This article shows a pharmaceutical dosage form designed by using LAPS as an API with pro-healing activity and its quality control. Pharmacotechnical and anti-microbial assays were adapted to demonstrate that the vehicle used does not modify LAPS activities. Selected formulation (F100) showed fair mechanical and technological properties. From the in vitro release assays was found an adequate release from the carrier matrix and maintains its anti-pathogenic activity for 6 months. We propose F100 for chronic wounds treatment. The use of harmless bacteria by-products, such as LAPS, to antagonize infectious pathogens that have ability to form biofilm is an efficient and economic approach to treat infected chronic wounds.